2001
DOI: 10.1074/jbc.m005370200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Vertebrate Nonmuscle Myosin IIB Isoforms Using Dictyostelium Chimeric Myosin II

Abstract: The alternatively spliced isoform of nonmuscle myosin II heavy chain B (MHC-IIB) with an insert of 21 amino acids in the actin-binding surface loop (loop 2), MHC-IIB(B2), is expressed specifically in the central nervous system of vertebrates. To examine the role of the B2 insert in the motor activity of the myosin II molecule, we expressed chimeric myosin heavy chain molecules using the Dictyostelium myosin II heavy chain as the backbone. We replaced the Dictyostelium native loop 2 with either the noninserted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 61 publications
2
18
0
Order By: Relevance
“…As Table 2 shows, in the absence of MLC 20 phosphorylation, there was no significant movement (Ͻ0.01 m/s) of actin filaments bound to HMM II-C0-and II-C1-coated surfaces. Following MLC 20 phosphorylation, as expected, the actin filaments were propelled by HMM II-C0 and II-C1 with an average velocity of 0.04 and 0.09 m/s, respectively, similar to a previous report (26). In contrast, HMM II-C2 and II-C1C2 can translocate actin filaments with a velocity of 0.06 m/s whether or not MLC 20 is phosphorylated.…”
Section: Actin-activated Mgatpase Activity Of Hmm Ii-c Isoforms-supporting
confidence: 64%
See 2 more Smart Citations
“…As Table 2 shows, in the absence of MLC 20 phosphorylation, there was no significant movement (Ͻ0.01 m/s) of actin filaments bound to HMM II-C0-and II-C1-coated surfaces. Following MLC 20 phosphorylation, as expected, the actin filaments were propelled by HMM II-C0 and II-C1 with an average velocity of 0.04 and 0.09 m/s, respectively, similar to a previous report (26). In contrast, HMM II-C2 and II-C1C2 can translocate actin filaments with a velocity of 0.06 m/s whether or not MLC 20 is phosphorylated.…”
Section: Actin-activated Mgatpase Activity Of Hmm Ii-c Isoforms-supporting
confidence: 64%
“…vertebrate NM IIs and smooth muscle myosin II (SM II) is regulated by phosphorylation of MLC 20 . These myosins have a very low actin-activated MgATPase activity when their light chain is unphosphorylated, and this activity increases upon phosphorylation of MLC 20 on Ser-19/Thr-18.…”
Section: Actin-activated Mgatpase Activity Of Hmm Ii-c Isoforms-mentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the effect of the B2 insert depends on the specificity of myosin heavy chain. In an experiment more directly relevant to the present report, Takahashi et al [21] introduced loop 2 from II-B0, and separately loop 2 from II-B2, into the Dictyostelium myosin II backbone replacing the endogenous loop 2. They found that introducing the II-B0 loop 2 lowered the actin-activated MgATPase activity by one-half compared to the wild-type activity and that introducing the II-B2 loop 2 reduced it by twothirds.…”
Section: Discussionmentioning
confidence: 99%
“…A further detailed study by Murphy and Spudich [20] showed that the V max of the actin-activated MgATPase activity and the affinity of Dictyostelium myosin for actin are both affected by substitutions of the loop 2 sequence. Takahashi et al [21] demonstrated that the insertion of the human II-B2 sequence into the Dictyostelium MHC reduced the motor activity of Dictyostelium myosin, with reduction of both the maximal actin-activated MgATPase activity and a decrease in the affinity for actin. In vivo studies with genetically ablated NMHC II-B2 mice demonstrated impaired motor coordination and misplaced Purkinje cells in the cerebellar molecular layer [13].…”
Section: Introductionmentioning
confidence: 99%